2017
DOI: 10.1519/jsc.0000000000001160
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Responses to Unilateral, Bilateral, and Alternating Limb Resistance Exercise Performed Using Different Body Segments

Abstract: Moreira, OC, Faraci, LL, de Matos, DG, Mazini Filho, ML, da Silva, SF, Aidar, FJ, Hickner, RC, and de Oliveira, CEP. Cardiovascular responses to unilateral, bilateral and alternating limb resistance exercise performed using different body segments. J Strength Cond Res 31(3): 644-652, 2017-The aim of this study was to verify and compare the cardiovascular responses to unilateral, bilateral, and alternating limb resistance exercise (RE) performed using different body segments. Fifteen men experienced in RE were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
3
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 21 publications
1
14
3
5
Order By: Relevance
“…Similar to our study, another recent investigation [24] compared CVR to unilateral, bilateral and alternating limbs for biceps curls, knee extensions and barbell rows, all performed at 80 % of 10RM with matched concentric/eccentric time. The authors reported no difference between unilateral and bilateral exercises, with the exception of the biceps curl, which induced a higher HR during the bilateral than the unilateral protocol.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Similar to our study, another recent investigation [24] compared CVR to unilateral, bilateral and alternating limbs for biceps curls, knee extensions and barbell rows, all performed at 80 % of 10RM with matched concentric/eccentric time. The authors reported no difference between unilateral and bilateral exercises, with the exception of the biceps curl, which induced a higher HR during the bilateral than the unilateral protocol.…”
Section: Discussionsupporting
confidence: 77%
“…Although some studies have shown that cardiovascular stress may be higher during exercises performed until fatigue with larger than smaller muscle groups [11,18], others could not detect differences in SBP, DBP, HR and RPP between unilateral and bilateral knee extensions [23,24,28], or between biceps curls and knee extensions [7]. Methodological features might account for those discrepant results, such as differences across protocols in the duration of total exercise [18,23,24] or concentric/eccentric phases [18] or type of muscle fibers [7,22]. For instance, MacDougall et al [18] observed that the peak pressure response was lower when a rela-tively smaller muscle mass (biceps curl) was employed in comparison to a larger one (single-or double-leg press).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cabe destacar que nos primeiros 30 segundos essa redução deve-se predominantemente à reentrada vagal 8 , sendo provável que essas respostas sejam ainda dependentes do tipo, volume e intensidade do exercício. Neste contexto, a maior parte dos estudos sobre as respostas da FC nos transientes inicial e final engloba quase unicamente os exercícios de natureza aeróbia 7 , ao passo que as investigações acerca dos exercícios de força não costumam observar essa variável, limitando-se apenas às medidas absolutas pré e pós-exercício 9 .…”
Section: Introductionunclassified